Zika Virus Infection With Prolonged Maternal Viremia and Fetal Brain Abnormalities. Issue 1 (March 2017) - Driggers, R.W.; Ho, C.-Y.; Korhonen, E.M.; Kuivanen, S.; Jääskeläinen, A.J.; Smura, T.; Rosenberg, A.; Hill, D.A.; DeBiasi, R.L.; Vezina, G.; Timofeev, J.; Rodriguez, F.J.; et al.
Abstract : ( N Engl J Med. 2016;374:2142–2151) Zika virus (ZIKV), a mosquito-borne flavivirus, is associated with intrauterine or perinatal transmission and increased risk of having a newborn with microcephaly. In the present study, the authors present findings on a case of congenital ZIKV infection in a pregnancy that was terminated at 21 weeks gestation.